Our house - a musical love story - Madness; Suggs; Warchus, Matthew (Universal Pictures, 2004)
Filming of the West End stage musical featuring the songs of Madness. Based in 1980s Camden Town, the musical tells the story of London lad Joe Casey, who on the night of his sixteenth birthday commits a petty crime to impress his girlfriend. The musical follows the two courses his life might have taken had he stayed to face the music when the police arrive at the scene, or if he had bunked the law by making a run for it. The musical won the 2003 Olivier Award for Best New Musical.